Application of Deep Breathing Relaxation Therapy as an Effort to Overcome Anxiety and Stress in the Community of RW 11 in Gebang sub-district, Patrang District, Jember: Penerapan Terapi Relaksasi Nafas Dalam Sebagai Upaya Mengatasi Kecemasan dan Stres pada Masyarakat RW 11 di kelurahan Gebang Kecamatan Patrang Jember (AgroNurse Kesehatan : Jurnal Pengabdian Masyarakat, 2024)
The World Health Organization stated that stress can be a primary threat to human mental health. Stress can contribute 50%-70% to the emergence of metabolic and hormonal diseases, hypertension, cancer, infections, cardiovascular diseases, skin diseases and so on. Stress involves transactions between individuals and the outside world. Stress is a response that arises if an individual assesses the event as stressful in terms of testing the ability to control the stressor and the subjective experience of stress. One way to improve psychological well-being is relaxation technique therapy. This method of community service activities is carried out by providing stress management health education and progressive muscle relaxation training to the community. This activity was guided by professional nursing students and there were additional media posters for stress management and progressive muscle relaxation to help people practice independently. The result of this activity is that the people who take part become more relaxed and anxious